Role of Aβ-RAGE interaction in oxidative stress and cPLA2 activation in astrocytes and cerebral endothelial cells - Askarova, Sholpan; Yang, Xiaoguang; Sheng, Wenwen; Sun, Grace Y.; Lee, James C-M. (Neuroscience. Author manuscript; available in PMC, 2012)
Blood–brain barrier (BBB) dysfunctions have been implicated in the progression of Alzheimer's disease. Cerebral endothelial cells (CECs) and astrocytes are the main cell components of the BBB. Although amyloid-β oligomers (Aβ42) have been reported to mediate oxidative damage to the CECs and astrocytes and trigger the downstream mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) pathway, the cell surface binding site for Aβ42 and exact sequence of these events have yet to be elucidated. In this study, the receptor for advanced glycation endproducts (RAGE) was postulated to function as a signal transducing cell surface receptor for Aβ42 to induce reactive oxygen species (ROS) generation from NADPH oxidase and trigger downstream pathways for the phosphorylation of extracellular signal-regulated kinases (ERK1/2) and cytosolic phospholipase A2 (cPLA2). We found that Aβ42 competed with the anti-RAGE antibody (AbRAGE) to bind to RAGE on the surfaces of CECs and primary astrocytes. In addition, AbRAGE abrogate Aβ42-induced ROS production and the colocalization between the cytosolic (p47-phox) and membrane (gp91-phox) subunits of NADPH oxidase in both cell types. AbRAGE as well as NADPH oxidase inhibitor and ROS scavenger suppressed Aβ42-induced ERK1/2 and cPLA2 phosphorylation in CECs. At the same time, only AbRAGE, but neither NADPH oxidase inhibitor nor ROS scavenger, inhibited the ERK1/2 pathway and cPLA2 phosphorylation in primary astrocytes. Therefore, this study demonstrates that NADPH oxidase complex assembly and ROS production are not required for Aβ42 binding to RAGE at astrocytic surface leading to sequential phosphorylation of ERK1/2 and cPLA2, and suggests the presence of two different RAGE-dependent downstream pathways in the CECs and astrocytes.
Keywords: Aβ-receptor; oxidative stress; cerebral endothelial cells; Research Subject Categories::MEDICINE::Microbiology, immunology, infectious diseases